Bilirubin as a predictor of severity and adverse clinical outcomes of acute ischemic stroke: a systematic review and meta-analysis - Ying Zhong; Lei Li (BMC Neurology)
Abstract Background This review aims to comprehensively examine the role of bilirubin in predicting severity and adverse clinical outcomes in patients with acute ischemic stroke (AIS). Methods We searched the electronic PubMed, Embase, Scopus, and Web of Science repositories for articles published in English available before the 15th of June 2024. The outcomes assessed were stroke severity, haemorrhagic transformation, symptomatic intracranial haemorrhage (sICH), mortality, and poor functional results. Results We analysed data from 13 studies. Our meta-analysis showed that both total bilirubin (RR, 1.10; 95% CI, 1.01–1.19) and direct bilirubin (RR, 1.79; 95% CI, 1.33–2.42) were independently associated with the severity of AIS. Higher quartiles of total bilirubin were associated with an increased risk of haemorrhagic transformation, but without statistical significance (RR, 2.34; 95% CI, 0.90–6.07). In addition, each unit increase in direct (RR, 1.25; 95% CI, 1.09–1.43) and indirect (RR, 1.09; 95% CI, 1.02–1.17) bilirubin levels was significantly associated with a higher risk of haemorrhagic transformation. Moreover, each unit increases in total (RR, 1.08; 95% CI, 1.04–1.12), direct (RR, 1.28; 95% CI, 1.13–1.44), and indirect (RR, 1.10; 95% CI, 1.03–1.18) bilirubin levels was significantly associated with a higher risk of sICH. Data on mortality and poor functional outcomes were insufficient. Conclusion Serum bilirubin levels were positively associated with the severity of AIS. The evidence suggests that bilirubin may be a potential indicator for haemorrhagic transformation and sICH after AIS.